Ku80 interaction with apurinic/apyrimidinic sites depends on the structure of DNA ends - Kosova, A.A.; Khodyreva, S.N.; Lavrik, O.I. (Вiopolymers and Cell, 2014)
Aim. The identification of a protein from human cell extract which specifically interacts with the apurinic/apyrimidinic (AP) site in the partial DNA duplex containing 5'and 3'-dangling ends (DDE-AP DNA) and mimicking clustered DNA damage. Methods. The Schiff base-dependent cross-linking of a protein to AP DNA (borohydride trapping), MALDI-TOF-MS, chromatography, and gel electrophoresis. Results. A human cell extract protein which forms a major covalent adduct with the AP DNA duplex with dangling ends was identified as the Ku80 subunit of Ku antigen by peptide mass mapping based on MALDI-TOF-MS data. The Ku antigen purified from the HeLa cell extract was shown to form the covalent adducts with the same mobility as observed in cell extracts. Conclusions. The Ku80 subunit of Ku antigen can specifically interact with AP DNA forming the Schiff base-mediated adducts which electrophoretic mobility depends on the structure of DNA ends. The difference in electrophoretic mobility can be caused by the cross-linking of AP DNA to distinct target amino acids that appears to reflect unequal positioning of AP DNAs in the complex with Ku antigen.